Silencing SOCS3 Markedly Deteriorates Spondyloarthritis in Mice Induced by Minicircle DNA Expressing IL23 - Chen, Yuhai; Ouyang, Jing; Yan, Ruoxiang; Maarouf, Mohamed Hassan; Wang, Xuefei; Chen, Biao; Liu, Shasha; Hu, Jiayue; Guo, Guijie; Zhang, Jing; Dai, Sheng-Ming; Xu, Huji; et al. (Frontiers in Immunology, 2018)
Objective: Despite extensive studies, the precise mechanism underlying spondyloarthritis, especially ankylosing spondylitis, remains elusive. This study aimed to develop an ideal animal model for an insight into mechanism of spondyloarthritis and functional relevance of SOCS3 in spondyloarthritis. Methods: Since SOCS3 is a major regulator of IL23-STAT3 signaling, we generated SOCS3 knockdown transgenic (TG) mice for development of an animal model of spondyloarthritis. A hydrodynamic delivery method was employed to deliver minicircle DNA expressing IL23 (mc-IL23) into wild-type (WT) and the TG mice. Knockdown/overexpression systems mediated by lentivirus and retrovirus were used to determine whether SOCS3 regulated osteoblast differentiation. Results: Forced expression of IL23 induced severe joint destruction and extensive bone loss in SOCS3 knockdown TG mice, while this treatment only caused moderate symptoms in WT mice. Furthermore, severe spondyloarthritis was found in IL23-injected TG mice as compared to mild disease observed in WT controls under same condition. Moreover, our studies showed that IL23 promoted osteoblast differentiation via activation of STAT3 pathway and disruption of SOCS3 expression greatly increased phosphorylation of STAT3. In addition, silencing SOCS3 resulted in enhanced osteoblast differentiation through activation of Smad1/5/9 signaling, as evidenced by elevated phosphorylation level of Smad1/5/9. Experiments further demonstrated that SOCS3 interacted with Smad1 and thus suppressed the BMP2-Smad signaling. Conclusions: The results reveal that SOCS3 is involved in IL23-induced spondyloarthritis and acts as a key regulator of osteoblast differentiation, and suggest that SOCS3 knockdown TG mice may be an ideal animal model for further studies of spondyloarthritis.